Laparoscopic Exploration of the Common Bile Duct and T-Tube Drainage in China (Journal of Chittagong Medical College Teachers' Association, 2016)
Biliary stones that are seen in the Asian population are very different from those seen in the west. It is frequent to see multiple, large, and impacted stones and a hugely dilated Common Bile Duct (CBD). Many of these patients have been managed by open cholecystectomy, even after the advent of Laparoscopic Cholecystectomy (LC) because these large stones pose significant challenges for extraction by endoscopic retrograde cholangio-pancreatography. This study represents an experience of managing intra and extra hepatic bile ducts using a laparoscopic approach. A retrospective data analysis was done during the period of November 2010-April 2015 and correspondingly 85 patients with documented intra and extra hepatic biliary stones were treated laparoscopically at Qilu Hospital under Shandong University, School of Medicine. There were 23 men and 62 women patients with age ranging from 23 to 76 years. The mean diameter of the CBD was 12mm. The number of stones extracted varied from 1 to 35 and the size of the extracted stones from 0.3X0.3X0.3 to 4X3.5X3.5 mm. The average duration of surgery was 170 min. There were 7 conversions to open procedures and 24 patients (29%) had nonfatal postoperative complications. Four patients had retained stones (4.7%). Though patients presented with multiple and impacted CBD stones, laparoscopy presents a unique approach for a minimally invasive procedure with its benefits in the form of laparoscopic intra and extra hepatic bile ducts exploration.  JCMCTA 2015 ; 26 (2) : 53 - 61